Tingkat Partisipasi Masyarakat Dalam Pengelolaan Hutan Mangrove Di Desa Purworejo Kabupaten Lampung Timur - Ferina Wati; Safe'i, Rahmat; Hari Kaskoyo; Rudi Hilmanto (Jurnal Hutan dan Masyarakat, 2023)
Community participation in Purworejo mangrove forest management activities is very important to support forest sustainability. Until now, community participation in mangrove forest management is still not optimal. This study aims to obtain the level of community assessment in the stages of managing mangrove forests in Purworejo Village. The method used was interviewing 31 respondents and data analysis using a Likert Scale. Research data shows that the level of community participation at the planning stage is in the low category with a proportion of 51.6%. The implementation stage is in the high category with a proportion of 41.9%. Stages of utilization are in the medium category with a proportion of 45.2%. Maintenance stages are in the low category with a proportion of 58.1%. Thus, the level of community participation in managing mangrove forests in Purworejo Village is in the low category with a proportion of 77%. So that community participation must be increased to support sustainable forest management